Pengembangan Media Jigsaw Puzzle Pendidikan Pancasila Berbasis Model Cooperative Learning Tipe Student Team Achievement Division di Sekolah Dasar - Ranti Satriani Putri; Muhammad Fachri Adnan; Muhammadi Muhammadi; Mutiara Felicita Amsal (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This research was motivated by students' lack of understanding of Pancasila Education learning materials due to the lack of engaging and interactive learning media, which leads to boredom, inactivity, and low learning outcomes. Therefore, interactive and educational learning media are needed to improve cognitive abilities and student engagement. The objective of this research was to develop a jigsaw puzzle media based on the STAD model that is valid, practical, and effective for Pancasila Education learning in fourth-grade elementary schools. This research employed a research and development (R&D) method using the ADDIE model, which consists of the following stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used to collect data for this development included a validity instrument, a practicality instrument, and an effectiveness instrument. The validity test results from the three validator experts were categorized as "Very Valid." Furthermore, the practicality test results from teacher and student responses at SDN 14 Laban and SDN 23 North Painan were categorized as "Very Practical." The results of the pretest of students in class IV A of SDN 14 Laban and students in class IV B of SDN 23 Painan Utara, both learning activities 1 and 2, experienced an increase after the posttest. Thus, the jigsaw puzzle media based on the STAD model in Pancasila Education learning in class IV of Elementary School has been declared valid, practical, and effective for use in learning.